2019
DOI: 10.1136/bmj.l6109
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes at follow-up of negative colonoscopy in average risk population: systematic review and meta-analysis

Abstract: ObjectiveTo review and summarise the evidence on the prevalence of colorectal adenomas and cancers at a follow-up screening colonoscopy after negative index colonoscopy, stratified by interval between examinations and by sex.DesignSystematic review and meta-analysis of all available studies.Data sourcesPubMed, Web of Science, and Embase. Two investigators independently extracted characteristics and results of identified studies and performed standardised quality ratings.Eligibility criteriaStudies assessing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
(132 reference statements)
1
21
0
Order By: Relevance
“…A recent systematic review and meta-analysis reported ADN prevalences at follow-up colonoscopy within 10 years of approximately 3%. 3 The overall prevalences in our study (4.1%-6.4% within 1-10 years) were well within the range of ADN prevalences (0.6%-9.4%) of the 28 studies included in the review. Only little evidence for even longer intervals is available.…”
Section: Findings In Contextsupporting
confidence: 82%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis reported ADN prevalences at follow-up colonoscopy within 10 years of approximately 3%. 3 The overall prevalences in our study (4.1%-6.4% within 1-10 years) were well within the range of ADN prevalences (0.6%-9.4%) of the 28 studies included in the review. Only little evidence for even longer intervals is available.…”
Section: Findings In Contextsupporting
confidence: 82%
“…Patients were classified according to the most advanced of the following findings: CRC, advanced adenoma (defined as presence of at least 1 adenoma with at least 1 of the following features: >1 cm in size, tubulovillous or villous components, high-grade dysplasia) other adenoma, hyperplastic or unspecified polyp, or none of these. 3,4…”
Section: Data Collectionmentioning
confidence: 99%
“…These guidelines are based on recent evidence [ 8 , 9 , 10 , 11 , 12 ] showing that the long-term CRC risk in patients with non-advanced neoplasia is not higher than that in the general population. If organized screening is not available, the repetition of colonoscopy 10 years after a negative colonoscopy is recommended [ 13 , 14 ]. However, these guidelines have been recently published; no previous standard definition for post-colonoscopy CRC was available.…”
Section: Introductionmentioning
confidence: 99%
“…Heisser and colleagues’ (doi:10.1136/bmj.l6109) linked meta-analysis of colorectal cancer and adenoma prevalence in the years following a negative colonoscopy shows that while neoplasms (including adenomas) were observed in more than 20% of participants within five years, advanced neoplasms were rare even after 10 years (2.1% in men, 1.8% in women) 1. The authors concluded that a 10 year screening interval after negative colonoscopy, as currently recommended,2 could be adequate 1…”
mentioning
confidence: 99%
“…Both studies used empirical analyses to assess outcomes following colonoscopy, identify substantial variations in expected outcomes, and explore potential sources of heterogeneity. Heisser and colleagues showed that the risk of advanced neoplasia after negative index colonoscopy is low 1. Extending the testing interval or the use of non-invasive alternatives such as triage by immunochemical testing might be appropriate for many of these patients, because they are least likely to benefit from repeat colonoscopy based screening.…”
mentioning
confidence: 99%